Effect of Electronic Cigarette on Oral Health - Haneen A. alyaseen / Zainab A. Aldhaher ((Humanities, social and applied sciences) Misan Journal of Academic Studies, 2024)
A vape, often known as an electronic cigarette, is a device that mimics tobacco use. The most popular tobacco products used by youth are electronic cigarettes and vape pens, in this research suggested that flavored liquid of electronic cigarettes have a negative effect on teeth and may cause other oral health problems. The e-cigarette has gained popularity all around the world since its release in 2003, most frequently in young individuals (18–25 years old). The term "smoking" gave rise to the term "vaping," which describes breathing an aerosolized "e-liquid" that has been evaporated without burning thanks to a small electronic vaporizer device. The aim of this study is to describe electronic cigarettes and their components, as well as to highlight the hazards of e-cigarette smoking on human health, regarding their safety; their impact on smoking initiation and smoking cessation; and regulatory issues related to their use. The scientific databases Scopus, Google Scholar, PubMed, and Web of Science can be searched using relevant keywords to find relevant papers. In conclusion electronic cigarette have an impact on oral and general health.